FBM successfully organized the 5th Advances in Business Research International Conference (ABRIC 2023) - UiTM, Faculty of Business and Management (UiTM, 2023)
Faculty of Business and Management (FBM), Universiti Teknologi MARA (UiTM), successfully organized the 5th Advances in Business Research International Conference 2023 (ABRIC 2023) at Resorts World Langkawi on September 27, 2023. This conference, coorganized with Fakultas Ekonomika and Bisnis, Universitas Negeri Surabaya, Faculty of Business, Universitas Multimedia Nusantara, and Faculty of Business Management and Professional Studies Management and Science University (MSU), Shah Alam. ABRIC 2023 provided a platform for academicians, researchers, professionals, and postgraduate students to share new ideas in research, engage in global interactions and commercialization of ideas, and create an international research network. It was such an honor for ABRIC 2023 to receive support from their co-organizers to ensure the conference has regional and global visibility.